Improving Reading French Based on Text Ability through Linguistic Functional Systemic for Students of State University of Medan - Tengku Ratna Soraya; Emzir Emzir; Sabarti Akhadiah (STKIP Singkawang, 2018)
This research aims to find out the process as well as the result of improving students’ ability in reading French texts through the approach of Linguistic Functional Systemic at Teaching French Study Program at Faculty of Arts and Language, State University of Medan. This study uses a Linguistic Functional Systemic approach with the assumption that the LFS approach examines the text used as a learning material in the course of Text Review / Etude de Texte . This approach proved able to answer various linguistic issues, either micro or macro. The research methodology used is action research developed by Kemmis & Mc Taggart with four steps: (1) planning, (2) action implementation, (3) observation, and (4) reflection. This study lasted for three cycles. In the first cycle, results were obtained as 21 students or 43.75% of 48 students earned grades above the prescribed minimum standards. Furthermore, in the second cycle the number of students who score above the minimum standard increases to 73%, and at the end of the third cycle to 85,42% students. The results of this study show that the LFS approach is very effective in helping students improve the reading ability of French texts. This research recommends to the lecturers of French courses in general understanding and using the LFS approach in the teaching and learning process of reading class in the classroom as in the subject of Text Review / Etude de Texte and Compréhension Ecrite.